Optimización del proceso de extracción hidroalcohólica a partir del orégano (Origanum vulgare L.). - Gavilanez Montesdeoca, Sixto Alejandro (2020)
This work was carried out with the purpose of optimizing the hydroalcoholic extraction process of the raw drug from the “oregano” plant; Therefore, the plant was dehydrated in a Universal 30 model stove for a time of 4 hours at a temperature of 40 ° C and the humidity was determined by the ML-40 Thermo-balance equipment that allowed to check the final humidity resulting from 12,09 %. The runs were established by the Desig Expert 8.0.6 program in which I determine 19 runs with different factors such as: time (6 h, 15 h and 24 h), temperatures (30 ° C and 60 ° C) and mass / solvent ratio (1:10 and 1:20). The oregano being an aromatic plant has phenolic compounds that are made up of organic acids as antioxidants. According to the analysis of the phytochemical profile carried out, they stand out in their composition: flavonoids, triterpenes, quinines, saponins, alkaloids, reducing sugars, phenolic compounds in greater proportion. By submitting the crude drug to a hydroalcoholic solution, the total polyphenol content and antioxidant capacity of the different experimental runs with the different factors were determined. The optimized extract was presented 10491.4 mg / L of antioxidant capacity, value superior to the total polyphenols 100.814 mg / L of the hydroalcoholic extract by numerical optimization and when checking these results, the antioxidant capacity is similar, and in terms of value of the total polyphenols is less than the numerical optimization value